INTEGRATION OF IMPORTANCE-PERFORMANCE ANALYSIS (IPA) AND KANO IN IMPROVING SERVICE QUALITY IN PDAM DISTRICT PENAJAM PASER UTARA - Herliana Rosalin; Doddy Adhimursandi (Politeknik Negeri Bengkalis, 2021)
PDAM District Penajam Paser Utara is a company engaged in the service sector. In the service sector, service quality must be considered to meet customer satisfactions who use these services. PDAM districts Penajam Paser Utara has tried to provide the best service. However, there are still complaints from customers, so research is needed using Integration Importance-Performance Analysis (IPA) and Kano to prioritize what attributes should be improved, maintained, and reduced. The results show that the quadrant I research category is the main priority to increase E3 complaints and suggestions that are well responded to, T1 air cleanliness, T4 air sufficiency, RS1 the responsiveness of officers if customer complaints, RS2 officers' willingness to provide the needed assistance, A1 guarantees officers to provide services are polite and friendly, and E1 information given to customers is clear.